Whistle variability in South Atlantic spinner dolphins from the Fernando de Noronha Archipelago off Brazil - Camargo, Fernanda S.; Rollo, Mario M.; Giampaoli, Viviana; Bellini, Claudio (Acoustical Soc Amer Amer Inst Physics, 2006)
A series of quali- and quantitative analyses were conducted to evaluate the variability of spinner dolphin whistles from the Fernando de Noronha Archipelago off Brazil. Nine variables were extracted from each whistle contour, and the whistle contours shapes were classified into the seven categories described in Driscoll (1995). The analysis showed mean beginning and ending frequencies values of 10.78 and 12.74 kHz, respectively. on average, whistle duration was relatively short, with mean values around 0.495 s (N=702). Comparative analyses were also conducted to investigate the relationship between the obtained results and those presented in previous studies. When comparing averages, the results of the study of Oswald et al. (2003) in the Tropical Eastern Pacific (TEP) presented less significant differences in relation to this study; only whistle duration differed significantly between both works. The results of multivariate classification tests also pointed TEP population as the closest related to the population studied here. The similarities between such disjunct populations might be attributed to a more recent isolation event (the closing of the Panama Isthmus) than the divergence that has driven North and South Atlantic populations apart. (c) 2006 Acoustical Society of America.